Proc. 27th Annual Conference of the International Group for Lean Construction (IGLC) 2019
DOI: 10.24928/2019/0239
|View full text |Cite
|
Sign up to set email alerts
|

How Stochastic Cost Estimates Could Be Applied in Relation to Target Value Design

Abstract: Approaches like Target Value Design (TVD) has gained more and more attention in the Construction Industry. Critical issues with these principles are how the cost targets are set, how shared profit is agreed upon and made transparent, and how production costs are steered towards the target costs and tracked. Research has shown positive applications of TVD, but also remaining challenges with the approach. This paper will focus on the process of setting the cost targets in TVD. In traditional design processes, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Some researchers claim that the target cost should be lower than the allowable cost for both project alliancing and Integrated Project Delivery (Sakal, 2005;Fischer et al, 2017). Torp (2019) has studied how public agencies in Norway set cost targets. In Norway, both the Norwegian Public Roads Administration and Statsbygg (the Norwegian government's principal advisor in construction and property affairs) use steering targets lower than the allowable cost.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers claim that the target cost should be lower than the allowable cost for both project alliancing and Integrated Project Delivery (Sakal, 2005;Fischer et al, 2017). Torp (2019) has studied how public agencies in Norway set cost targets. In Norway, both the Norwegian Public Roads Administration and Statsbygg (the Norwegian government's principal advisor in construction and property affairs) use steering targets lower than the allowable cost.…”
Section: Introductionmentioning
confidence: 99%
“…This benchmarking process uses historical information which must specify project-specific elements in order to achieve a realistic maximum project cost. Torp (2019) concluded that stochastic estimates can be applied for setting Allowable Cost (P85) and estimating Expected Cost (P50).…”
Section: Cost Estimationmentioning
confidence: 99%
“…Os autores propõem diretrizes para a implementação da metodologia nesse contexto, mas não deixam claro como os custos de mercado são definidos. O custo de mercado é a saída do modelo de custo e estimado pela equipe do projeto (TORP, 2019).…”
Section: Introductionunclassified